History of Coronary Angiography - Wake, Ryotaro; Yoshiyama, Minoru; Iida, Hidetaka; Takeshita, Hiroaki; Kusuyama, Takanori; Kanamitsu, Hitoshi; Mitsui, Hideya; Yamada, Yukio; Shimodozono, Shinichi; Haze, Kazuo (IntechOpen, 2011)
None